Equidistribution of integers represented by standard quadratic form under arithmetic constraints - Ma, Yefei (2025)
We study the equidistribution of integers of the form$n= x_1^2 + … + x_d^2$under the arithmetic constraints given by$(\mathbb{Z}/p\mathbb{Z})^d$ . The first step in addressing this problem is to construct modular forms whose Fourier expansion coefficients correspond to the counting problem over the quadric in$\mathbb{Z}^d$induced by the standard quadratic form, subject to the aforementioned arithmetic constraints. The weak modular property of these modular forms allows us to use representation theory to identify the congruence subgroup to which our modular forms correspond. We then establish a necessary and sufficient condition for functions on$(\mathbb{Z}/p\mathbb{Z})^d$that defines a cusp form. Finally, we conclude that the equidistribution phenomenon occurs locally on$p+1$orbits for$d ≥ 4$ .